Technics and human development - Mumford, Lewis (A Harvest / HBJ Book, 1966)
Contents: Mumford explains the forces that have shaped technology since prehistoric times and shaped the modern world. He shows how tools developed because of significant parallel inventions in ritual, language, and social organization. “It is a stimulating volume, informed both with an enormous range of knowledge and empathetic spirit” (Eliot Fremont-Smith, New York Times). Index; photographs.